2020
DOI: 10.4314/jae.v24i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of mobile phone for marketing of cereals by smallholder farmers in Quang Dien District of Vietnam

Abstract: The study investigated factors that shape the Vietnamese smallholders’ adoption of mobile phones for marketing. A random sample of 161 smallholders was drawn from a total of 275 smallholders who produced and marketed cereals in Quang Dien district of Vietnam. Percentages, means, standard deviations, chi squares test, t-test and a binary logistic regression model were applied to analyse the data. This study concluded that the young male smallholders with a higher education level, who are members of community-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Those farmers with more farming experience tend to use technology more than those with less experience (Abebe and Mammo Cherinet, 2018). This might be that longer experience in farming increase exposure to ICTs that is used in agricultural activities including market access (Hoang, 2020).…”
Section: Farmers' Attributes Regarding Mobile Phone Usementioning
confidence: 99%
See 3 more Smart Citations
“…Those farmers with more farming experience tend to use technology more than those with less experience (Abebe and Mammo Cherinet, 2018). This might be that longer experience in farming increase exposure to ICTs that is used in agricultural activities including market access (Hoang, 2020).…”
Section: Farmers' Attributes Regarding Mobile Phone Usementioning
confidence: 99%
“…Mobile phones have the potential to amplify the speed and ease, and to introduce new ways of sharing information. The use of mobile phones in agriculture has already been known to increase production (Abraham, 2007;Jensen, 2007;Bhavnani et al, 2008;Nakasone et al, 2014;Ogbeide and Ele, 2015;Amir et al, 2016;Hoang, 2020;Thimnu, 2020). Phones can enable interactive communication flow unhindered by space, volume, medium or time, thereby influencing the existing communicative ecologies (Deribe, 2016;Misaki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implication here, is that respondents who had higher level of training and education were in the category of adopters of water conservation practice. This finding is supported by the study of Hoang, G.H. (2020), found that educated farmers appreciate and adopt the use of mobile phone in marketing cereals than the uneducated farmers.…”
Section: Dependence Of Adoption Of Water Conservation Practices On Somentioning
confidence: 56%